Agronomic iron-biofortification by activated hydrochars of spent coffee grounds - Lara-Ramos, Leslie; Fernández-Bayo, Jesús; Delgado, Gabriel; Fernández-Arteaga, Alejandro (Frontiers in Sustainable Food Systems, 2023)
Iron biofortification has been of main interest for tackling iron deficiency anemia, one of the highest prevalence among micronutrient deficiencies (hidden hunger) in developing countries. This study investigated the effect of activated spent coffee grounds (SCG) and its hydrochars at three temperatures (160ºC, 180ºC, 200ºC) as bio-chelates to level up the iron content of lettuce. Four bio-chelates (ASCG-Fe, AH160-Fe, AH180-Fe and AH200-Fe) were obtained by activation and Fe-functionalization. A pot trial was conducted at doses of 0.2% of the bio-chelates on lettuce with two controls: soil without biofortifying agents (control) and a commercial chelate (control-Fe). Outcomes showed no significant differences (p <0.05) in soil properties nor in plant growth and morphology, indicating absence of phytotoxicity. All bio-chelates enhanced iron content of plants between 41% (AH200-Fe) and 150% (AH160-Fe) compared to control. The best biofortification effect performed by AH160-Fe was similar to control-Fe (169%), also in terms of soil-plant efficiency both products showed the same transfer factor of 0.07. A proportional impact (up to 150%) was seen on the contribution to the recommended daily intake (RDI). Moreover, higher contents of Mn (29%) and Cu (133%) was evidenced in lettuce with the application of ASCG-Fe and AH180-Fe. These findings suggest activated SCG hydrochars, better than SCG, at small (sub-toxic) doses can successfully achieve agronomic iron biofortification.